Behavior of grout injected solid stone masonry walls under in-plane loading - Dinc-Sengonul, Burcu; Yuzer, Nabi; Sengonul, Caner; Ulukaya, Serhan; Oktay, Didem; Undul, Omer (ELSEVIER SCIENCE INC, 2023)
It is a shared duty of all humanity to ensure the preservation of historical structures for future generations. The discontinuities, cracks, and gaps in the masonry walls, especially in historical structures, prevent the building from working monolithically. For this reason, historical buildings need repair and strengthening efforts in time. Grouting is an effective technique for consolidating and strengthening masonry structures. This study aims to establish a general evaluation of the injection method used to repair damaged stone walls. For this purpose, solid stone masonry walls were constructed and tested under in-plane loading to simulate the actual conditions. The solid stone masonry walls are made of saw-cut travertine stones and plastered with English bond, a pattern formed by laying alternate courses of stretchers and headers. The mechanical behavior of the solid stone masonry walls, both in non-damaged condition and with grout injected into the cracks caused by the preloading, was monitored and demonstrated in terms of the load-displacement relationship. As a result of the wall tests, it was observed that there was an increase of up to 28% in the maximum lateral load that the walls can withstand without any crack formation after grout injection.
Keywords: Grouting; Mechanical behavior; Stone masonry walls; Historical structures; Lime-based mortars; HYDRAULIC LIME GROUTS; TEMPERATURE; SUSPENSIONS; PARAMETERS; DESIGN; REPAIR; Engineering